Structure and dynamics of iron pentacarbonyl - Portius, Peter; Bühl, Michael; George, Michael W.; Grevels, Friedrich-Wilhelm; Turner, James J. (2020)
The dynamics of CO ligand scrambling in Fe(CO)5 has been investigated by linear infrared spectroscopy in supercritical xenon solution. The activation barrier for the Berry pseudorotation in Fe(CO)5 was determined experimentally to be Ea = 2.5 ± 0.4 kcal mol–1 by quantitative analysis of the temperature-dependent spectral line shape. This compares well with the range of Ea/(kcal mol–1) = 2.0 to 2.3 calculated by various DFT methods and the value of 1.6 ± 0.3 previously obtained from 2D IR measurements by Harris et al. ( Science 2008, 319, 1820). The involvement of Fe(CO)5···Xe interactions in the ligand scrambling process was tested computationally at the BP86-D3/AE2 level and found to be negligible.